2014
DOI: 10.31018/jans.v6i2.530
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme changes during seed storage in groundnut (Arachis hypogaea L.)

Abstract: A change in enzyme activity in seeds due to ageing is a topic of scientific importance. Vigour is essentially a physiological phenomenon influenced by the reserved metabolites, enzyme activities and growth regulators. The exact cause of loss of seed vigour and viability is still unknown as deterioration of seed is a complex process. In the presence of oxygen, ageing of seed can lead to peroxidative changes in polyunsaturated fatty acids. The free radical -induced non-enzymatic peroxidation, which has the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The activity of lipase enzyme increased during storage from 0.231 to 0.236 (meq min -1 g -1 of sample). It might be due to the secretion of fungal lipase of the storage fungi which increased the rate of lipid degradation (Junaithal Begum et al, 2014) From the results of these investigations, it could be concluded that the seed lots which had higher vigour were able to maintain their storability for longer duration and retain higher quality parameters than low vigour seed lots.…”
Section: Resultsmentioning
confidence: 98%
“…The activity of lipase enzyme increased during storage from 0.231 to 0.236 (meq min -1 g -1 of sample). It might be due to the secretion of fungal lipase of the storage fungi which increased the rate of lipid degradation (Junaithal Begum et al, 2014) From the results of these investigations, it could be concluded that the seed lots which had higher vigour were able to maintain their storability for longer duration and retain higher quality parameters than low vigour seed lots.…”
Section: Resultsmentioning
confidence: 98%
“…But the percent decrease was less in T 13 (15% for peroxidase and 4% for catalase activity) while the high per cent increase was observed in T 1 (59% for peroxidase and 21% for catalase activity) (Fig 5 and 6). Begum et al (2014) stated that reduction in catalase and peroxidase activity was highly evident in case of groundnut where the reduction in peroxidase enzyme activity was from 0.236 to 0.444 OD 10 min -1 during higher storage periods. The reduced antioxidant defense system was associated with inability of the seeds to repair the damage caused by ageing and seed deterioration (Mittler, 2002;Mullan and McDowell, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The longevity of stored seed is affected by a number of factors and the four major factors are seed moisture content, temperature, relative humidity and oxygen concentration in the storage environment. High temperature and high relative humidity cause rapid deterioration of viability and vigour of groundnut seeds (Begum et al, 2014). Seeds with high oil content appear to lose their germination and vigour in a very short time in spite of the precaution taken during harvesting and drying.The lipids in groundnut seeds are at risk of auto-oxidation, which contains oleic (18:1), linoleic (18:2) and linolenic (18:3) fatty acid chain.…”
Section: Introductionmentioning
confidence: 99%